Effects of organic amendments and fertilizers on biomass yield, bioactive compounds and heavy metals content of Phyllanthus niruri L. - Ab Razak, Zahidah (2017)
Soil amendment using organic materials such as chicken manure and/or biochar may potentially improve the soil physico-chemical properties, and crop production. Both biochar and chicken manure are commonly used for alleviating the infertility of highly weathered soil. The general aim of this study was to determine optimum rate of soil amendment and investigate effects of rice husk biochar and chicken manure as a soil amendment on biomass yield, bioactive compounds, nutrient uptake and heavy metals concentration of Phyllanthus niruri. A polybag study was conducted with treatments of three rates of biochar application (0, 5 and 10 t ha-1) and three rates of chicken manure (0, 2.5 and 5 t ha-1) laid out in Randomized Complete Block Design (RCBD) with four replications. Results showed that co-application of 10 t ha -1 biochar and 2.5 t ha-1 chicken manure produced optimum yield of Phyllanthus niruri which are 1720.80 mg plant-1 and higher phyllanthin and hypophyllanthin contents (11.85 mg plant-1 and 12.77 mg plant-1). Application of biochar and chicken manure increased N, P and K uptake by 37% and 42% compared to control treatment. Application of chicken manure and biochar also able to reduce the heavy metal concentrations (cadmium and arsenic) in plant tissue. Application of chicken manure without biochar has produced about 5.25 to 8.89 mg kg-1 arsenic concentration (above Maximum Permissible Levels) in plant tissue compared to combination treatment between biochar and chicken manure which range between 3.06 to 5.06 mg kg-1. Cadmium and arsenic uptake by Phyllanthus niruri were below the Maximum Permissible Levels. There are about 40% increases in phyllanthin content and 34% increase in hypophyllanthin content with the selected rate of amendment. However, phyllantin and hypophyllanthin concentration in P. niruri was not affected both biochar and chicken manure amendment.